Renal Autotransplantation for Iatrogenic High-Grade Ureteric Stricture. (4th December 2012) - Soto Soto, Jose; Phillips, Michael; Cernigliaro, Joseph; Haley, William
Abstract : A 47-year-old Hispanic woman developed a chronically obstructed left kidney, due to a long-segment ureteric stricture deemed not amenable to reimplantation, following left ovarian cyst excision in 2004. Therefore, a ureteral stent requiring exchange every 3 months was necessary, due to hydronephrosis, recurrent urosepsis, chronic pain, and a poor quality of life. Her medical history was complicated by hypertension, poorly controlled diabetes mellitus, and microalbuminuria, suggesting early diabetic nephropathy. A left nephrectomy was recommended. This was deferred, due to concern for progressive kidney failure associated with her comorbidities. A radionuclide Tc-99m MAG3 renal scan revealed differential perfusion as follows: 44% left kidney and 56% right kidney, with symmetrical uptake on the renogram phase and delayed excretion on the left, which were correctted following furosemide administration. A left ureteronephrectomy with autotransplantation of the left kidney and ureteroneocystostomy was performed in 2009. Since then, the patient has experienced no further complications or need for invasive procedures, with excellent diabetic control and stable renal function (eGFR > 60 mL/min/1.73 m 2 ). This technique is seldom employed in the surgical management of complex ureteral injuries, but may be an alternative for appropriate cases.